Photocatalytic properties of T102-Al203 based nanocomposite prepared by hydrothermal method - Mansor, Ahmad Mustaqim (2018)
In this study, the photocatalytic properties of Tio2—Al2o3 nanocomposite prepared by hydrothermal method was investigated in terms of washing pH and addition of graphene. Hydrothermal synthesis was performed in temperature of 180°C for 40 hours in an autoclave. The composite was determined of its morphology, phase identification and photocatalytic performance of methyl orange degradation. Morphology of Tio2—Al2o3 and Tio2—Al2o3-graphene nanocomposites were agglomerated in more alkaline condition. The nanocomposites with graphene addition was well distributed compared to that of without graphene. The traces of a new phase were invisible in all composites. The composite which was washed at pH 9 showed greater absorbance of methyl orange at 45% under UV light.